Implementasi Kode Etik dalam Mewujudkan Mahasiswa Berkarakter dan Berprestasi - Rina Tiur Lona; Indra Syahputra Marpaung; Nurbaya Harianja ; Aris Munandar Harahap (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The current problem is that in an increasingly sophisticated era, student ethics are increasingly decreasing. One of the tasks of higher education is to create students with character and achievements. Thus, this research will examine the implementation of the student code of ethics and its implications in creating students with character and achievements. The aim of this research is to find out the process of implementing the code of ethics and its implications for students. The method used in this research is descriptive qualitative. The conclusion of this research is that the implementation of the student code of ethics has gone well and has positive implications in creating students with character and achievements, namely 70.71%. From the results of implementing the code of ethics, students have their own character and achievements which are viewed from aspects of student character and aspects of student achievement. In implementing the code of ethics, there are supporting and inhibiting factors.